New Prospects for the Management of Cardiovascular Effects of Tyrosine Kinase Inhibitors in Patients with Chronic Myeloid Leukemia - Almeida, A (2019)
The use of tyrosine kinase inhibitors (TKIs) for the treatment of chronic myeloid leukemia has significantly altered the prognosis of this disease, enabling close to normal life expectancy. Despite their undeniable benefits, the use of TKIs is associated with an increased risk of side effects on the cardiovascular system, particularly of atherothrombotic events. It is therefore necessary to understand and prevent the adverse effects of these drugs, in order to enable antileukemic therapy to continue and to minimize patients' toxic exposure. This multidisciplinary consensus document, developed through a collaboration between hematologists and cardiologists, aims to review the cardiovascular toxicity associated with various TKIs and to establish recommendations for the follow-up of these patients. Measures are also proposed for the assessment and reduction of cardiovascular risk in these patients and referral criteria, and relevant drug interactions are discussed.